Daily precipitation isotope variation in Midwestern United States: Implication for hydroclimate and moisture source - Bedaso, Zelalem; Wu, Shuang-Ye (The Science of the total environment, 2020)
Stable isotopes of oxygen (δ18O) and hydrogen (δD) in precipitation can be used as dual conservative tracers in the hydrologic cycle and help to understand hydrological and atmospheric processes. Although long-term monthly precipitation global isotope datasets are available in some locations, currently there are limited daily precipitation isotope data, particularly in the Midwest region of the USA. In this study we report a daily precipitation δ18O and δD dataset from March 2014–December 2017 in Dayton, Ohio, the USA. The daily δ18O and δD vary from −28.0 to 0.4‰, and −214.0 to 9.0‰ respectively. The data exhibit strong seasonality with lower δ18O and δD values in the winter and higher values in the summer. The precipitation isotopic values are mainly controlled by temperature, and show no correlation with precipitation amount and relative humidity. However, δ18O-temperature relationship varies among different seasons. The correlation is the strongest in winter (R2 = 0.56), weaker in spring (R2 = 0.28) and fall (R2 = 0.24), and almost non-existent in summer (R2 = 0.1). The slope values also vary with highest value in winter (0.68‰/OC) and much smaller in other seasons. The HYSPLIT back trajectory analyses show that Pacific, Gulf of Mexico, Arctic and Continental moistures are the main sources for southwestern Ohio with different seasonal contributions. The isotopic compositions of precipitation from different sources show small intra-season variations but large seasonal variability. Our daily-resolved dataset provides new insights into the main controls on the isotopic composition of precipitation and its seasonal variations, which could help to understand atmospheric processes and enable their proper use in interpretation of paleoclimate proxies, particularly those with seasonal bias. [Display omitted] •δ18O shows seasonality with high values in the summer and low values in the winter.•Precipitation isotopic composition is mainly controlled by temperature.•The δ18O-T relationship varies seasonally with highest slope in winter.•Dayton gets moisture from Pacific, Gulf of Mexico, Arctic and Continental sources.•δ18O from different sources are similar within a season but vary seasonally.